Scandal and the runaway bride - Alward, Donna (Harlequin Romance, 2020)
Will Pemberton's plan was simple: find Gabi, his brother's runaway bride, and protect his famous family from the press. Until their dangerous attraction threatens a bigger scandal! Gabi's wedding might have been fake, but Will's growing feelings for the misunderstood heiress are dangerously real. Falling for Gabi risks his family and the life he's worked hard to turn around. Is it one risk he's willing to take?